The USE OF ELECTRON SPECTRA IN DETERMINING THE COORDINATION NUMBER OF CENTRAL ATOMS OF COMPLEX COMPOUNDS BASED ON Ni(II) AND Co(II) IONS: USE OF ELECTRON SPECTRA IN DETERMINING THE COORDINATION NUMBER OF CENTRAL ATOMS OF COMPLEX COMPOUNDS BASED ON Ni(II) AND Co(II) IONS - Qo'chqorova, Ra'no (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article presents ideas on the identification of the central ion that forms the complex in complex compounds of nickel and cobalt with a coordination number of six.